Portable Video Media Versus Standard Verbal Communication in Surgical Information Delivery to Nurses: A Prospective Multicenter, Randomized Controlled Crossover Trial. Issue 5 (13th May 2016) - Kam, Jonathan; Ainsworth, Hannah; Handmer, Marcus; Louie‐Johnsun, Mark; Winter, Matthew
ABSTRACT: Background: Continuing education of health professionals is important for delivery of quality health care. Surgical nurses are often required to understand surgical procedures. Nurses need to be aware of the expected outcomes and recognize potential complications of such procedures during their daily work. Traditional educational methods, such as conferences and tutorials or informal education at the bedside, have many drawbacks for delivery of this information in a universal, standardized, and timely manner. The rapid uptake of portable media devices makes portable video media (PVM) a potential alternative to current educational methods. Objective: To compare PVM to standard verbal communication (SVC) for surgical information delivery and educational training for nurses and evaluate its impact on knowledge acquisition and participant satisfaction. Design: Prospective, multicenter, randomized controlled crossover trial. Setting: Two hospitals: Gosford District Hospital and Wyong Hospital. Participants: Seventy‐two nursing staff (36 at each site). Intervention: Information delivery via PVM––7‐minute video compared to information delivered via SVC. Outcome Measures: Knowledge acquisition was measured by a 32‐point questionnaire, and satisfaction with the method of education delivery was measured using the validated Client Satisfaction Questionnaire (CSQ‐8). Results: Knowledge acquisition was higher via PVM compared to SVC 25.9 (95% confidence interval [CI] 25.2‐26.6) versus 24.3 (95% CI 23.5‐25.1), p = .004. Participant satisfaction was higher with PVM 29.5 (95% CI 28.3‐30.7) versus 26.5 (95% CI 25.1‐27.9), p = .003. Following information delivery via SVC, participants had a 6% increase in knowledge scores, 24.3 (95% CI 23.5‐25.1) versus 25.7 (95% CI 24.9‐26.5) p = .001, and a 13% increase in satisfaction scores, 26.5 (95% CI 25.1‐27.9) versus 29.9 (95% CI 28.8‐31.0) p < .001, when they crossed‐over to information delivery via PVM. Linking Evidence to Action: PVM provides a novel method for providing education to nurses that improves knowledge retention and satisfaction with the educational process.